Language Training, Refugees’ Healthcare Integration, and the Next Generation’s Health - Dang, Thang (Elsevier, 2025)
Exploiting a policy reform mandating participation in a 300-hour language training course in Norway, I investigate the multigenerational health effects of a comprehensive language training program. I document the significant positive impacts of the program, not only on the long-term integration of refugees into the healthcare system but also on the health of the next generation. The program improves the cumulative use of primary care services for 12 years after arrival by 44%. This increase is proposed to partially work through refugees’ increased labor market attachment and economic success. The program also results in spillover benefits for the health at birth of the children of refugees with 21–49% decreases in premature birth, low birth weight, and short birth length. These intergenerational effects probably operate via significant improvements in the home environment and maternal care during pregnancy.
​​​​​​​